Therapeutic thoroughfares for adults living with Pompe disease. Issue 5 (8th October 2022) - Schoser, Benedikt; Laforet, Pascal
Abstract : Purpose of review: Pompe disease is caused by autosomal recessive mutations in the acid α-glucosidase gene leading to a multiorgan deficiency of the enzyme acid glucosidase alfa. To recover to a nondiseased status, a lift over a threshold of 25% acid glucosidase alfa enzyme activity is required. This update on therapeutic thoroughfares for adult Pompe disease aims to assist neuromuscular and metabolic specialists. Recent findings: We reviewed the recent studies covering enzyme replacement therapy, gene therapy, and substrate reduction therapy in adult Pompe disease. Results of phase 3 studies and the first sets of long-term data of both novel enzyme replacement therapies, avalglucosidase alfa, and ciplaglucodsidase alfa combined with miglustat, are public. First gene therapy trials are ongoing. Substrate reduction therapy is in early transition to the clinical trial phase. We still miss dose escalation and intensification of frequency trials on enzyme replacement therapy in adults, probably suitable to echo current results in infantile and juvenile Pompe disease. Summary: Therapy of Pompe disease reaches new thoroughfares reducing the overall disease burden of patients; however, individualization of these novel therapeutic options remains challenging. Consensus-based and shared decision-based recommendations need to be established based on reliable real-world data to allow the best standards of care worldwide.